Dolores Huerta Stands Strong : The Woman Who Demanded Justice - Brill, Marlene Targ (Book collections on Project MUSE., 2018)
Dolores Huerta Stands Strong follows Huerta's life from the mining communities of the Southwest where her father toiled, to the vineyards and fields of California, to the present day. As she advocated for farmworkers, Mexican American immigrants, women, and LGBTQ population rights, Dolores earned the nation's highest honors and found her voice.